Anti-microbial Susceptibility of Staphylococcus aureus Isolated from Different Clinical Infection - Enas Jalil Baqer Almayali (Journal of Global Pharma Technology, 2019)
This study investigated staphylococcus aureus in many of the infected clinical samples and their resistance to antibiotics .The study included two mainaxes, the first axis is diagnosis of bacterial isolates according to approved diagnostic systems, the second axis is determine the resistance and sensitivity of the antibiotic.  A total of 250 clinical samples were collected from several places of the body from Al-Hakim General Hospital and Al-Sadr city medical in Al-Najaf city during the period from November 2018-Febray 2019. Samples were under study (ear, eye, wound, urine, tonsils, diabetic foot and aspiration fluid) for both sexes and different age group. The results of the bacterial diagnosis showed that sample was infected with staphylococcus aureus (20 isolated from diabetic foot, 10 isolated from ear ,10 isolated from urine , 15 isolated from wound, 15 isolated from aspiration fluid),depending on characters of culture media, Gram stain, biochemical test and Vitek-2 for identification . The study also examined the sensitive test by testing disk diffusion depending on the locations of the disease. Isolated from ear, wound, diabetic foot, aspiration fluid were resistance to penicillin family. While isolated from urine were variable to it family. All isolated were sensitive to vancomycin, teicoplanin, impenem, meropenam. All isolated were sensitive to amikacin, refampine, except isolates from diabetic foot were resistant to it. Cefidinr more kind of cephalosporin gives sensitivity to study isolated. Quinolones, macrolides, aminoglycoside were variable depending on location of the disease.Keywords: S. aureus, Sensitivity